Motivating Factors of Youth Selecting Labor Migration Rather Than Higher Education: A Systematic Review - Mahato, Santosh K.; Paudel, Devi Prasad; Baral, Om Prasad (Interdisciplinary Research in Education, 2022)
There are many underlying factors those are compelling youths for selecting labor migration rather than continuing their higher education. Hence, to comprehend what factors aredeterring youths towards higher education in the context of Nepal, the studywas carried out. For that, researchers used a systematic review method and overviewed secondary sources likewise book, article, and research reports published in the similar area. Through this review, multiple and multi-dimensional factors i.e., social, cultural, economic, educational, political, environmental, and miscellaneous of youth labor migration were identified. In most cases,youths were compelled for the labor migration, however, in some cases, youth were migrated for pursuing education. Also, youth labor migration was found throughout the globe including Nepal. Finally, it was concluded that youth migration was varied and the context specific especially in the developed, developing, and underdeveloped countries, hence the trend and patterns of youth labor migration was diverse.